Some remarks on the absolute discontinuance of proceedings against offenders with small amounts of narcotics or psychotropic substances for personal use - Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In this article the author presents the evolution of the legal solutions applied to offenders offender of the crime “small” possession of drugs. Under the framework, a lot of space was devoted to the analysis of the new institution from Art. 62, Act, 2005 on counteracting drug addiction, which provides for the discontinuance of proceedings against the mentioned group of offenders. Referring to the statutory regulation there were also identified areas that prove defects identified in the adopted solutions and hence require rapid intervention from the legislator.
Keywords: posiadanie narkotyków lub substancji psychotropowych; bezwzględne umorzenie postępowania w stosunku do sprawców/sprawcy posiadania "niewielkiej" ilości